Nuevas instrucciones para los autores de la Revista Cubana de Medicina Militar - Quevedo Fonseca, Carlos Rafael; Corral Martín, Ariadna; Vázquez Velázquez, Elvia; del Risco Valiente, Gladys Inés; Lozano Hidalgo, Yudiana (Revista Cubana de Medicina Militar, 2024)
Nuevas instrucciones para los autores de la Revista Cubana de Medicina Militar